A systematic Failure Mode Effects and Criticality Analysis for offshore wind turbine systems towards integrated condition based maintenance strategies. (15th March 2019) - Scheu, Matti Niclas; Tremps, Lorena; Smolka, Ursula; Kolios, Athanasios; Brennan, Feargal
Abstract: Condition-based maintenance is applied in various industries to monitor and control critical assets and to optimize maintenance efforts. Its applicability to the offshore wind energy industry has been considered for almost 20 years and has resulted in the development and implementation of solutions that have contributed to lower cost of maintenance and increased asset availability. However, there is currently no public domain guidance available that provides the information required to (i) prioritize systems for which condition monitoring would generate highest value and to (ii) understand the parameters that need to be monitored by a specific system from failure cause to failure mode. Both items are addressed in this paper, providing a clearly structured, risk-based assessment methodology and corresponding results for state-of-the-art offshore wind turbines. A total of 337 failure modes have been identified and analysed by experts representing approximately 70% of the European offshore wind market to assess potential benefits of condition monitoring systems. Results may be used to target the development of condition monitoring systems focusing on critical systems and to find optimal O&M strategies by understanding failure paths of main offshore wind turbine systems resulting in a lower cost of energy and a more optimal risk-return balance. Highlights: Transparent risk-based methodology for prioritization of offshore wind turbine systems towards application of condition monitoring systems is presented. Critical failure modes of the main wind turbine systems are presented. Failure causes and mechanisms are presented (failure path)*failure pathinformation is not yet available in the public domain. Presented information contains comprehensive literature review involvement of more than 40 key experts from the European Offshore Wind community, representing approximately 70% of the installed capacity (this data basis is more recent and comprehensive than any other used in comparable papers). Results contain information about different types of wind turbines and substructure concepts at different sites making them usable for a variety of applications and representing the state-of-the-art today.